2005
DOI: 10.1159/000089995
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Cisplatin plus Capecitabine in Metastatic Breast Cancer Patients Heavily Pretreated with both Anthracycline and Taxanes

Abstract: Background: Treating patients with anthracycline- and taxane-pretreated metastatic breast cancer is challenging. This study evaluated the activity and safety of a combination of cisplatin and capecitabine in this setting. Patients and Methods: Thirty-nine consecutive patients entered the study. All had experienced failures or relapse after previous treatment with anthracyclines and taxanes plus/minus other chemotherapeutic regimens. The present treatment consisted of intravenous cisplatin 20 mg/m2 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
1
10
1
Order By: Relevance
“…Altogether, nausea/vomiting were the most common non-hematological toxicities and the incidence in our study appeared to be higher than previous reports. 18,19 Nevertheless, the majority of these events were presented as nausea only, with much less patients complaining about vomiting. Furthermore, most nausea/vomiting events occurred in the first cycle of XP regimen, and decreased with strengthened antiemesis therapy thereafter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, nausea/vomiting were the most common non-hematological toxicities and the incidence in our study appeared to be higher than previous reports. 18,19 Nevertheless, the majority of these events were presented as nausea only, with much less patients complaining about vomiting. Furthermore, most nausea/vomiting events occurred in the first cycle of XP regimen, and decreased with strengthened antiemesis therapy thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Besides, several studies evaluating the association of cisplatin and continuous infusion 5-FU have shown response rate ranging 11-48% in second-or third-line treatment, [14][15][16][17] and 62/ in first-line approach. 14 Additionally, 2 prospective trials 18,19 have obtained interesting results with the combination of cisplatin and capecitabine in unselected MBC patients pretreated with anthracyclines and/or taxanes, indicating an ORR range of 35.9-51.5%, PFS of 5.2-6.3 months and OS of 10.9-11.5 months.…”
Section: Introductionmentioning
confidence: 99%
“…Different schedules of the CapCisp combination for advanced breast carcinoma have been reported [18][19][20] . Donadio et al [18] reported an objective response rate of 35.9% (complete response 7.7%) and 10.9 months OS (16.5 months in responding cases) in 39 MBC patients pretreated with anthracycline and taxane with a regimen containing weekly Cisp and Cap.…”
Section: Discussionmentioning
confidence: 99%
“…Donadio et al [18] reported an objective response rate of 35.9% (complete response 7.7%) and 10.9 months OS (16.5 months in responding cases) in 39 MBC patients pretreated with anthracycline and taxane with a regimen containing weekly Cisp and Cap. The addition of epirubicin to Cisp and Cap (EXC regimen) as neoadjuvant chemotherapy in locally advanced or inflammatory breast carcinoma also improved the overall and complete response rates (74 and 13%) to the cost of chemotherapyinduced nausea/vomiting and hypercoagulable disorders [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Median TTP was 5.2 months and median OS was 10.9 months. The dose-limiting toxicity for the regimen was leukopenia, while gastrointestinal discomfort was the most frequent cause of capecitabine reduction or delay [126]. When cisplatin was replaced with oxaliplatin, the RR was 32%.…”
Section: Experience With Combination Chemotherapymentioning
confidence: 99%